An exploratory study of inclusive worksite wellness: Considering employees with disabilities. Issue 1 (January 2016) - Cook, LaWanda H.; Foley, John T.; Semeah, Luz Mairena
Abstract: Background: An increasing number of employers are offering worksite wellness programs, yet, little is known about the participation of workers with disabilities. Objective: The primary purpose of this study was to explore the factors, which facilitate and impede participation in worksite wellness offerings by individuals with disabilities. Methods: Participants completed the Access to Worksite Wellness Services to Employees with Disabilities (AWWSED). Results: The decision to participate in worksite wellness programs is influenced by several individual, social, and organizational factors including perceptions of the impact of one's disability on health, the health habits of coworkers, and an organizational commitment to employee well-being. Study participants also indicated the importance of affordability, convenient times, and interest in the wellness activities being offered, as influencing participation decisions. Conclusions: These findings suggest that individual, social, and organizational factors all contribute to the decision to participate and suggest that social support from colleagues as well as easily obtained and understandable program information from the employer, may be especially useful in engaging employees with disabilities in wellness programs.